Establishing the Soul Entrepreneurship of Women Groups in Processing Corn to Become Foods That A Sale Value - Usman Usman; Veneranda Rini Hapsari; Rissa Ayustia (Journal of International Conference Proceedings (JICP), 2019)
Corn farming is one of the fields expected to be able to be a pillar in order to improve community welfare. The role of agriculture is very large because agriculture is able to restore the nation's economic growth because of its enormous natural potential and the amount of uniformity which is a reliable sector that is able to develop well. This research is to provide education and motivation to the mothers of farmer groups in building an entrepreneurial spirit by reading opportunities or opportunities that exist. The writing method used is descriptive qualitative or describes all the events in the field and tells the solution of existing problems based on data obtained by the aim of providing an explanation of the variables examined. The focus of the study was to develop the entrepreneurial spirit of women or mothers or wives of corn farmers in Belimbing village. The data used are primary data because they are taken directly from data sources, namely the corn farmer mothers. The benefits of corn itself are very many because there are many nutritional contents and can reduce hypertension so as to prevent heart disease, and corn can also prevent disease diabetes and can prevent constipation and hemorrhoids.